A study of optimum aeration efficiency of a lab‐scale air‐diffused system. (2nd June 2017) - Al Ba'ba'a, Hasan B.; Amano, Ryoichi S.
Abstract: Up to now, tremendous efforts have been devoted to modelling the oxygen transfer coefficient (kL a) for diffused aeration systems, while not considering the corresponding energy consumption. Enhancing kL a is favorable for an exemplary oxygenation process, but may come at the cost of greater energy withdrawal, an unwelcome tradeoff. Assessing the aeration efficiency (the rate of oxygen delivered per unit energy) reflects the overall effectiveness of an aeration process and guarantees a superior system performance. Presented here is a lab‐scale study that investigates the effect of the orifice diameter, the airflow rate and the water column on the aeration efficiency. Various combinations of the studied parameters were tested using a cylindrical tank with a single orifice for air injection. An optimal performance of the aeration efficiency was observed at an orifice diameter of 0.3 mm when tested under 0.91 m water column and an airflow rate of 0.05 SLPM. Furthermore, a new empirical formula of aeration efficiency was established with a high correlation index ( R 2  = 0.97) to allow preliminary prediction of aeration efficiency.